Aggression in team sports A quantitative investigation of reversal theory motives - Fruchart, E.; Rulence-Pâques, P.; Mullet, E. (International Journal of Sport Psychology, 2020)
Two quantitative studies examined the structure of motives for aggression among players practising team sports (rink-hockey, handball, football, rugby, and basketball). METHOD: In both studies, the participants filled in a 48-item questionnaire that was created from all eight dimensions suggested by reversal theory. In study 1, Exploratory Factor Analysis was conducted. In study 2, Confirmatory Factor Analysis was performed. RESULTS: In the first study, a three-factor structure of motives was found: A Motives Related to Egocentrism factor, a Motives Related to Negativistic Reaction factor, and a Motives Related to Game Purpose factor. The second study confirmed the three-factor structure of motives for aggression in team sport. The mean scores observed for the Motives Related to Negativistic factor and the Motives Related to Game Purpose factor were higher than the Motives Related to Egocentrism factor. CONCLUSION: The results partially supported reversal theory-based predictions about multiple motives for aggression in sport.